1981
DOI: 10.1111/j.1095-8312.1981.tb01845.x
|View full text |Cite
|
Sign up to set email alerts
|

Density and environmental effects on shell size in some sand dune snail populations

Abstract: Populations ol three species of land snail, Helicella itala. Candidula intersecta and Cochlicella acuta are studied on sand dunes on Coll in the Inner Hebrides. Population density and mean shell size were estimated on 18 sample sites. The sites were ranked for six environmental factors. Environmental factors which are related to the dune vegetational succession account for much of the variation in the densities of C. intersecta and C. acuta. The density of H. itala, however, shows no strong association with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…There was no difference in the timing of oviposition by small and large adult snails. Crowding has also been shown to reduce the activity of some helicid snails (Cameron and Carter, 1979), but Tattersfield (1981) has suggested that the activity of C. acuta is not reduced by increased density. Density effects may be relatively unimportant in the ecology of C. acuta, if food is not limiting.…”
Section: Discussionmentioning
confidence: 99%
“…There was no difference in the timing of oviposition by small and large adult snails. Crowding has also been shown to reduce the activity of some helicid snails (Cameron and Carter, 1979), but Tattersfield (1981) has suggested that the activity of C. acuta is not reduced by increased density. Density effects may be relatively unimportant in the ecology of C. acuta, if food is not limiting.…”
Section: Discussionmentioning
confidence: 99%
“…Adult size has been shown to be negatively correlated with population density in several European helicids. The relationship has been shown in field surveys of Cepaea nemoralis (Cook & O' Donald, 1971; Williamson et al , 1976;Oosterhoff, 1977) and three other helicid species (Tattersfield , 1981).…”
Section: Population Densitymentioning
confidence: 79%
“…The Mollusca recovered from untreated sediment are given as Table 3. The basal sample (0.95-1.1 m) consists almost exclusively of Cochlicella acuta, a species typical of dunes and coastal grasslands (Kerney and Cameron 1979) and often associated with mobile or semi-fixed surfaces on dunes (Evans 1972;Tattersfield 1981). The lack of other species would also suggest a low-diversity environment, and a bare sand surface seems likely.…”
Section: Dune Palaeoenvironmental Developmentmentioning
confidence: 99%